Foreign direct investment attractiveness in terms of creating preconditions for effective cooperation between border regions - Nosova, Olga Valentinovna; ІvaschenkoPetr Alekseevich (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
Attractiveness of foreign direct investment (FDI) for effective cooperation between border regions is connected with checking hypothesis of mutual attraction of FDI in decision making process. It is t correlated with the mutual social, economic and environmental problems of the border regions. The paper proposes to determine FDI structure of funding sources by using the utility model.